2023
DOI: 10.1155/2023/6405415
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening, Antioxidant Activity, and Acute Toxicity Evaluation of Senna italica Extract Used in Traditional Medicine

Abstract: Medicinal plants such as Senna italica are increasingly used for their purgative virtues to treat stomach aches, fever, and jaundice. This study aims to screen the phytochemical compounds and to assess the antioxidant activity in vitro and the acute oral toxicity in vivo of Senna italica leaves. The plant was harvested, dried, pulverized, and preserved. Phytochemical screening was performed using different laboratory protocols. Ethanolic and aqueous extracts were, respectively, obtained by maceration and decoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(46 reference statements)
1
0
0
Order By: Relevance
“…This is also consistent with the low TPC content of Soxhlet extracts, where pure solvents were used. Similar results have been previously obtained on the TPC from various plant species, including Ziziphus mucronata stem bark [32], Senna italica leaves [33], almonds [34], walnuts [35], and several wild edible legumes [36]. Specifically, in these studies, it was observed that extraction with pure methanol and ethanol produced higher TPC values than the extraction with acetone.…”
Section: Acetone and Ethanol Are The Best Solvents For Flavonoids And...supporting
confidence: 87%
See 1 more Smart Citation
“…This is also consistent with the low TPC content of Soxhlet extracts, where pure solvents were used. Similar results have been previously obtained on the TPC from various plant species, including Ziziphus mucronata stem bark [32], Senna italica leaves [33], almonds [34], walnuts [35], and several wild edible legumes [36]. Specifically, in these studies, it was observed that extraction with pure methanol and ethanol produced higher TPC values than the extraction with acetone.…”
Section: Acetone and Ethanol Are The Best Solvents For Flavonoids And...supporting
confidence: 87%
“…mL −1 cell medium, ranged from 1141.97 ± 80. 33 Acetone extracts demonstrated higher inhibitory activity against the MCF-7 cell line, while HeLa and HepG2 cell lines showed lower sensitivity. While MA50 and MA70 showed comparable activity on HeLa and HepG2 cells, MA50 was more active than MA70 on MCF-7 cells.…”
Section: Hydroalcoholic Extracts Show the Highest Radical Scavenging ...mentioning
confidence: 93%